PENGARUH GREEN PRODUCT, GREEN PROMOTION, DAN ECO-LABEL TERHADAP GREEN PURCHASE INTENTION PADA PRODUK INNISFREE DALAM PERSPEKTIF BISNIS ISLAM (STUDI PADA PENGGUNA PRODUK INNISFREE DI KOTA BANDAR LAMPUNG) - Rahmawaty, Soffiyah Putri; Anita, Siska Yuli; Hasimi, Diah Mukminatul (Papanda Publisher, 2025)
This research aims to analyze the influence of green product, green promotion, and eco-label on green purchase intention on innisfree products, from an Islamic business perspective. Amidst increasing awareness of enviromental issues, the use of environmentally friendly products is becoming increasingly popular, one of which is Innisfree products. This study uses a quantitative approach by collecting data through distributed questionnaires with a total of 100 respondents. For statistical tests and data processing were using Partial Least Square (SmartPLS version 4). Based on the research results, it can be concluded that Green Product and Green Promotion have a positive and significant influence on Green Purchase Intention on Innisfree products, while Eco-Label does not show a significant influence partially. Green Product is the dominant factor that drives consumer purchase intention, indicating that product quality and sustainability are highly considered in purchasing decisions. Green Promotion has also proven effective in attracting consumer interest, especially through campaigns that highlight environmental concerns. However, Eco-Label has not been able to provide a strong influence, possibly due to low consumer awareness of the meaning and importance of the environmental label.